Implementation of guideline recommendations and outcomes in patients with idiopathic pulmonary fibrosis: Data from the IPF-PRO registry. (November 2021) - de Andrade, Joao A.; Kulkarni, Tejaswini; Neely, Megan L.; Hellkamp, Anne S.; Case, Amy Hajari; Guntupalli, Kalpalatha; Bender, Shaun; Conoscenti, Craig S.; Snyder, Laurie D.
Abstract: Background: Few data are available on the extent to which clinical practice is aligned with international guidelines for the management of idiopathic pulmonary fibrosis (IPF). We investigated the extent to which management guidelines for IPF have been implemented in the US IPF-PRO Registry and associations between implementation of guidelines and clinical outcomes. Methods: We assessed the implementation of eight recommendations in clinical practice guidelines within the 6 months after enrollment: visit to a specialized clinic; pulmonary function testing; use of oxygen in patients with resting hypoxemia and exercise-induced hypoxemia; referral for pulmonary rehabilitation; treatment of gastro-esophageal reflux disease; initiation of anti-fibrotic therapy; referral for lung transplant evaluation. An implementation score was calculated as the number of recommendations achieved divided by the number for which the patient was eligible. Associations between implementation score and outcomes were analyzed using logistic regression and Cox proportional hazards models. Results: Among 727 patients, median (Q1, Q3) implementation score was 0.6 (0.5, 0.8). Patients with an implementation score >0.6 had greater disease severity than those with a lower score. Implementation was lowest for referral for pulmonary rehabilitation (19.5%) and lung transplant evaluation (22.3%). In unadjusted models, patients with higher implementation scores had a greater risk of death, death or lung transplant, and hospitalization, but no significant associations were observed in adjusted models. Conclusions: Management guidelines were more likely to be implemented in patients with IPF with greater disease severity. When adjusted for disease severity, no association was found between implementation of management guidelines and clinical outcomes. Graphical abstract: Image 1 Highlights: We investigated the implementation of guidelines for the management of IPF. Guidelines were more likely to be implemented in patients with more severe disease. In adjusted models, there were no associations between guideline use and outcomes.